2016
DOI: 10.4149/bll_2016_061
|View full text |Cite
|
Sign up to set email alerts
|

Dominant neurologic symptomatology in intravascular large B-cell lymphoma

Abstract: Intravascular large B-cell lymphoma (IVLBCL) is a rare variant of extranodal large B-cell lymphoma and it is characterized by selective intravascular proliferation of malignant cells. Typical features of the disease include aggressive behavior, rapid and frequently fatal course. Clinical picture is non-specifi c and heterogeneous, depending on the affected organ. It is not uncommon that this unique type of lymphoma is diagnosed post mortem. Herein, we report two cases of IVLBCL with neurologic symptomatology. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…[ 4 ] The most frequent laboratory test results of IVLBCL are anemia, high erythrocyte sedimentation rate, and elevated LDH. [ 14 ] Although various patterns of abnormal features on brain MRI in patients with IVLBCL have been reported, a recent study suggested the findings on brain MRI were categorized into 4 patterns: (1) non-specific white matter lesions, (2) infarct-like lesions, (2) hyperintense lesions in the pons, and (4) meningeal thickening and/or enhancement. [ 15 ] In contrast, brain MRA is not useful in the diagnosis of IVLBCL as affected cerebral vessels are too small to be directly shown on MRA.…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 ] The most frequent laboratory test results of IVLBCL are anemia, high erythrocyte sedimentation rate, and elevated LDH. [ 14 ] Although various patterns of abnormal features on brain MRI in patients with IVLBCL have been reported, a recent study suggested the findings on brain MRI were categorized into 4 patterns: (1) non-specific white matter lesions, (2) infarct-like lesions, (2) hyperintense lesions in the pons, and (4) meningeal thickening and/or enhancement. [ 15 ] In contrast, brain MRA is not useful in the diagnosis of IVLBCL as affected cerebral vessels are too small to be directly shown on MRA.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that although any organ may be involved, neurological signs and symptoms are the most common presentation of the disease [ 3 8 ]. Neuropathic deficits are very heterogeneous, including mental status changes, transient ischemic attack, paraparesis of the extremities, and defect in motor functions [ 9 , 10 ]. In the current study, central nervous system, bone marrow, pericardium, liver, skin, small bowel, and fallopian tube and ovary were organs with biopsy-proven involvement by lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…Brain magnetic resonance imaging (MRI) reveals normal findings or nonspecific hyperintense lesions in the white matter, suggestive of demyelination or ischemic pathology by small vessel occlusion. [8][9][10] Laboratory tests are usually nonspecific. Malignant lymphoid cells are only occasionally found in the peripheral blood smear or in the cerebrospinal fluid, where an increased protein level and/or lymphocytosis are more common although unspecific.…”
Section: Introductionmentioning
confidence: 99%
“…Malignant lymphoid cells are only occasionally found in the peripheral blood smear or in the cerebrospinal fluid, where an increased protein level and/or lymphocytosis are more common although unspecific. 8,10 Intra vitam diagnosis is particularly difficult due to the rapid course of the disease, the lack of involvement of lymph nodes and bone marrow, and the unspecific clinical, laboratory and imaging findings. Biopsies are needed to reach a diagnosis, but their success depends on lymphoma localization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation